Capital market and economic growth in Malaysia / Fatin Nuratiqah Hasbullah - Hasbullah, Fatin Nuratiqah (2022)
Capital market is a fact that can be found in each contemporary economy. It is a market whose necessity cannot be questioned, constantly adapting to the economic environment while also influential. Thus, one that generates opportunities while also posing risks to all categories of participants in economic activity. The goal of this research is to examine the influence of Malaysia's capital market on economic development. We will investigate the link between economic growth and the independent variables identified in this research, including Sukuk, convertible bonds, and Sukuk and convertible bonds. This study will look at the influence of the capital market on economic development over ten years, from 201 1 to 2020. The secondary will be using will utilize secondary data in this study, which has been published and may be accessed from past publications and papers. The Eviews application is being utilized to quantify the result. The multiple linear regression test is carried out using the t-test and the f-test. R-squared and normality tests also included R-squared and normality tests in the assumption test.